2020
DOI: 10.1007/s11423-020-09776-3
|View full text |Cite
|
Sign up to set email alerts
|

“Instructional disobedience”: a largely neglected phenomenon deserving more systematic research attention

Abstract: Education is characterized by at least the following features: (a) it offers learning environments that help students to achieve preset goals, (b) it induces learners to engage in relevant learning tasks, and (c) it offers support while learners execute learning tasks. Offering learning environments builds on the assumption that learners will actually engage in the learning tasks and use the support provided. There is, however, growing evidence (e.g., Almeda, Baker, & Corbett, 2017; Koc & Liu, 2016), that in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…No differences in exam results were found based on instructional strategy meaning we cannot confirm our hypothesis that ML leads to superior learning outcomes. The fact that there was no difference in the test scores of students between instructional conditions, while the activities of these students significantly differed, seems to be illustrative of what Elen [4] has called "instructional disobedience". This indicates that while the quantity of learning activity can be influenced relatively easily through the design of the learning environment, the quality is not.…”
Section: Discussionmentioning
confidence: 90%
“…No differences in exam results were found based on instructional strategy meaning we cannot confirm our hypothesis that ML leads to superior learning outcomes. The fact that there was no difference in the test scores of students between instructional conditions, while the activities of these students significantly differed, seems to be illustrative of what Elen [4] has called "instructional disobedience". This indicates that while the quantity of learning activity can be influenced relatively easily through the design of the learning environment, the quality is not.…”
Section: Discussionmentioning
confidence: 90%
“…Based on students’ qualitative feedback, we have reasons to believe that students did not always work in the learning environment as we would want them to do. Thus, students did not interact with the need support in the intended way (‘instructional disobedient behavior’: Elen, 2020 ). For example, several students reported that they did not always read all the material, did not make use of the forum, or did not notice certain messages from the researcher.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this study clearly elaborates on the operationalizations of need support used, and as such, might inform instructional designers in order to implement need support in an integrated manner (including competence, relatedness and autonomy support). Future interventions might want to track and monitor students’ learning behavior in order for students to interact with the learning environment as expected (Elen, 2020 ). Thirdly, this study established theoretical relationships between students’ needs, motivation and cognitive outcomes, which might be useful information for researchers aiming to investigate students’ motivation towards learning research skills in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We use the term ‘activity’ to mean ‘what students are actually doing’ – mentally, physically and emotionally – during a period of time in which they are meant to be learning something (a learning episode or ‘at learn-time’). For better or worse, what students actually do may differ considerably from what their teachers think they are doing or what their teachers intend them to do (Goodyear 2000 ; Ellis and Goodyear 2010 ; Elen 2020 ; Koh and Kan 2020 ).…”
Section: Acad: Definition and High Level Descriptionmentioning
confidence: 99%